Study on Preparation of Nano Humic Acid and Adsorption Effect of Heavy Metals in Soil - Qian Sun; Kamaruddin, Mohamad Anuar Bin; Kai Huang; Yun Cao; Mohd Suffian Yusoff; Yong Cheng (Emerging Science Journal, 2025)
Nano humic acid (NHA) offers a promising strategy for remediating agricultural soils contaminated by livestock and poultry manure. This study investigates the adsorption behavior of NHA for heavy metals (Cu, Zn, As, Mg) and nitrogenous compounds (nitrate and ammonium nitrogen) in real-world polluted soil collected from a poultry farm in Changzhou, China. NHA was synthesized via high-shear, acid-precipitation, and surfactant-assisted methods, and its structure was characterized using scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), and particle size analysis. FTIR revealed the emergence of new functional groups (e.g., amino, ester, sulfonic), enhancing the active sites available for pollutant binding. At 30 days, NHA treatments achieved substantial reductions in Cu (76.1%), Zn (57.5%), and As (12.9%), with NANO3 and NANO4 showing the highest adsorption capacity. At 90 days, Cu and Mg continued to exhibit strong dose-responsive removal (up to 49.9% and 26.8%, respectively), while Zn and As showed nonlinear responses, likely due to saturation effects. NHA also outperformed traditional humic acid in nitrate and ammonium nitrogen adsorption, with the 25 g/kg application (NANO2) achieving up to 55% nitrate and 20% ammonium reduction. Correlation analysis confirmed that material type, rather than dosage alone, was the dominant factor influencing pollutant immobilization. These findings demonstrate that NHA is an effective, dual-function soil amendment capable of long-term remediation of both heavy metal and nitrogen pollution, offering a cost-effective and scalable solution for improving soil quality in degraded agricultural regions such as the Yellow River basin.